Signs of a missed root canal - M. Yu. Pokrovsky; O. A. Aleshina; T. P. Goryacheva; A. M. Pokrovskiy (Эндодонтия Today, 2023)
Aim. To describe the radiological signs of a "missed" root canal when using CBCT based on verified clinical cases. Materials and methods. The study is based on the analysis of cases of endodontic treatment, which are associated with the detection of a "missed" root canal detected intraoperatively at the stage of primary endodontic treatment or at the stage of endodontic revision (repeated endodontic intervention). Clinical cases were verified by detecting the root canal during endodontic treatment using a microscope. Results. During the endodontic treatment of 2149 teeth, 506 "missed" canals were identified and verified using a microscope. Based on the comparison of cone-beam computed tomography data and clinical data obtained during the examination of teeth under a microscope, 7 signs of the presence of a "missed" root canal are described. General recommendations are given to improve the quality of root canal system diagnostics. Conclusions. The presented information contributes to improving the accuracy of diagnosis, proper planning and improving the effectiveness of endodontic treatment not only in endodontic revision (repeated root canal treatment), but also in primary endodontic treatment.